UPAYA MENINGKATKAN HASIL BELAJAR PKn DENGAN PENERAPAN MODEL KOPERATIF SKRIP SISWA KELAS VI SDN 005 BUKIT KAPUR KECAMATAN BUKIT KAPUR - Abdullah ' (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the low student learning outcomes Civics Class VI SDN 005Bukit Kapur. This study aims to describe the results of learning by using the cooperativemodel script. The subjects were students of class VI SDN 005 Bukit Kapur consisting of twocycles. The data in this study focuses on improving learning outcomes. The instrument usedfor data collection is an oral test and a written test in the form of worksheets that do after thelearning process. Results showed absorption learning outcomes on average 93% in subjectscategorized Civics very good, very effective learning effectiveness categorized by an averageof 93%. While completeness of student learning outcomes otherwise completed 100%.